Multi-rate Input Based Model Predictive Control for Permanent Magnet Synchronous Motor - Xu, Peng; Xiao, Jian; Dan, Yuanhong (Journal of Electrical Systems, 2018)
Based on the multi-rate digital control theory and the model predictive control theory, in consideration of the dynamic response speed mismatch between the current loop and the speed loop of permanent magnet synchronous motor field-oriented control system, multi-rate input model predictive controller of PMSM in the single loop is proposed. Simulation and experimental results show the effectiveness of the algorithm, and furthermore, the algorithm can ensure the whole control system performance under the data-loss situation.